COMPLEX FOR NON-DESTRUCTIVE ELEMENTAL ANALYSIS OF SOLID-STATE MATERIALS WITH NANOMETER RESOLUTION - Komarov, F. F.; Kamyshan, A. S.; Danilevich, V. V.; Boiko, E. B.; Kupchishin, A. I.; Togambayeva, A. K. (Recent Contributions to Physics, 2009)
A measuring system for non-destructive elemental analysis of materials, providing the registration of Rutherford backscattering spectra with an energy resolution of 1.3 % has been designed and established. Thiscorresponds to a minimal thickness of examined layer of 1.0–1.5 nm. A cylindrical electrostatic nonhomogeneous-field spectrometer is a main part of this system.
Keywords: energy resolution